Images of Childhood and Children in Early Photobooks: Capturing Reality and Expectations / Photography in Children’s Literature (Elina Druker and Bettina Kümmerling-Meibauer, Eds., 2023) - Dang, Quynh (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2024)
Photography in Children’s Literature, edited by Elina Druker and Bettina Kümmerling-Meibauer (John Benjamins, 2023) offers a transnational investigation of children’s photography spanning from the early 1870s to the late 1980s. It sets itself apart from many counterparts because of its wide range of analyzed topics, genres, and artistic techniques. This edited volume is recommended for all researchers and scholars interested in the transnationality of childhood politics and how photographs and children’s picturebooks play a vital role in promoting powerful transnational children’s images.